P593Human vascular pericytes and cardiac progenitor cells combined transplantation for heart repair. (15th July 2014) - Avolio, E; Mangialardi, G; Riu, F; Katare, R; Mitchell, K; Dang, Z; Spencer, H; Meloni, M; Beltrami, AP; Madeddu, P
Abstract: Purpose: to compare the regenerative potential of Saphenous Vein-derived Pericytes (SVPs) with that of c-Kit-pos Cardiac Progenitor Cells (CPCs) in a mouse model of myocardial infarction (MI), and to investigate if the simultaneus transplantation of the cells produces additive improvements. Methods: CPCs were isolated from discarded atrial specimens of transplanted hearts; SVPs were immune-sorted from vein leftovers of CABG patients. Cells were compared in vitro according to their surface-phenotype and differentiation ability toward the 3 cardiac lineages. The functional recovery of SCID-Beige mice infarcted hearts injected with Vehicle (n=6), CPCs (n=6), SVPs (n=6) or CPCs+SVPs (n=6) (300, 000 cells of each type/heart) was compared, both 14 and 42 days post-MI. Interaction between SVPs and CPCs, secretomes, and paracrine effects were investigated in vitro. Results: both SVPs and CPCs express mesenchymal markers (CD44/CD90/CD105), are negative for endothelial and hematopoietic antigens and express the stemness markers Sox2. In addition, SVPs express the pericyte markers NG2 and PDGFRb. Both cell types secrete similar paracrine factors (HGF, VEGF, FGF, SCF), supplemented by Ang-1 and -2 regarding SVPs. Importantly, co-culture of cells for 48h increased the secretion of SDF-1. CPCs differentiate in endothelial and vascular muscle cells, while both cell types acquire cardiomyocyte markers when exposed for 21 days to an inductive culture medium. Cell transplantation similarly improved volume, contractility and pressure indexes at 14 and 42 days post-MI compared to vehicle, with no additive effect by combined therapy. Similarly, myocardial healing was stimulated by both the cell types, protecting cardiomyocytes from apoptosis and increasing the density of endogenous CPCs; the combined therapy did not add further improvements. When exposed to SVP conditioned media, CPCs tend to increase migration compared to plain media. This response is not abrogated or diminished by RNAase or tyrosine and serine/threonine kinase receptor inhibitors, or a blocking antibodies cocktail (HGF, FGF, VEGF, SCF, and Tie2). Proteinase K pretreatment was able to abrogate the response, differently from the heating denaturation. Fractioning SVP conditioned medium by molecular weight showed that secreted chemoattractant factor is >10 kDa. Conclusions: SVPs are therapeutically equipotent to CPCs. The more accessible source makes SVPs an optimal alternative to CPCs in cell therapy for myocardial repair. Moreover, the attractant effect on CPCs in the site of injury favours the endogenous cardiac regeneration.